2018
DOI: 10.1186/s12913-017-2822-y
|View full text |Cite
|
Sign up to set email alerts
|

“Ways and channels for voice regarding perceptions of maternal health care services within the communities of the Makamba and Kayanza provinces in the Republic of Burundi: an exploratory study”

Abstract: BackgroundIncreased availability of maternal health services alone does not lead to better outcomes for maternal health.The services need to be utilized first.One way to increase service utilization is to plan responsive health care services by taking into account the community’s views or expressed needs.Burundi has a high maternal mortality ratio, and despite improvements in health infrastructure, skilled staff and the abolition of user fees for pregnant women,utilization of maternal health services remains l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Though there is a dearth of quantitative research on community perceptions on the quality of maternal care, it has been explored by a few qualitative studies. Similar with other studies, we find that community members have poor perceptions of quality of maternal care ( 27 , 28 ). A possible reason for these poor perceptions is the perceived lack of emotional support women receive from healthcare providers ( 29 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though there is a dearth of quantitative research on community perceptions on the quality of maternal care, it has been explored by a few qualitative studies. Similar with other studies, we find that community members have poor perceptions of quality of maternal care ( 27 , 28 ). A possible reason for these poor perceptions is the perceived lack of emotional support women receive from healthcare providers ( 29 ).…”
Section: Discussionsupporting
confidence: 90%
“…One interpretation of this finding relates to the idea of hierarchical social relations (28). Given that literacy is closely related to one's family social status, it could be that community members with a lower literacy level have poorer perceptions of supportive care because they witness the social stigma their female relatives experience within the healthcare system (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, doubts as to whether this system is effective. Indeed, the scant research in Burundi has noted that HFC members are rarely supported and aware of their tasks and roles and that there is an apparent disconnect between the HF staff, the catchment area population, and their committees (Falisse et al 2012;Niyongabo et al 2018).…”
Section: Local Elite and Health Facility Committees In Burundimentioning
confidence: 99%
“…They also need to have the genuine possibility to influence the HF, which stems not only from their knowledge but also depends on "systematic asymmetries of power inherent in unequal societies" (Osmani 2008, p. 38). Pointing to the negligible influence of committee members at their HF (Falisse et al 2012;Niyongabo et al 2018), the research on HFC in Burundi suggests a power gap: HFC members have limited influence over HF staff members. By throwing their weight behind the committee, local elites may potentially help narrow such a gap.…”
Section: Local Elite and Health Facility Committees In Burundimentioning
confidence: 99%
“…1,20 Information sources also play a role in contraception uptake. [22][23][24] In our study, medical personnel were the most frequently reported source of information about contraception, over neighbours, radio or television, and the Church. In rural Malawi, it has been shown that the media can play a significant role in improving maternal health outcomes when it is community-led and locally driven.…”
Section: Discussionmentioning
confidence: 78%